"I'm More Open to Talking About It": Women's Experiences With Sexual Abuse and Reproductive Health. Issue 23 (December 2021) - Meier, Stephanie; Brig, Kristin; Delay, Cara; Sundstrom, Beth; Schwab-Reese, Laura; DeMaria, Andrea L.
Approximately one in three women experience sexual abuse, which can result in negative reproductive health consequences. A history of sexual abuse may negatively impact health care seeking and experience. The purposes of this article were to understand how women perceived their sexual abuse experiences and how these experiences integrated into their overall reproductive health, reproductive planning, and health care access. As part of a larger study about women's reproductive health, researchers analyzed 16 in-depth interviews with women aged 18 years and older (range = 18–78) living in South Carolina (May–November 2016). A constant comparative method of data analysis was completed to explore women's sexual abuse experiences as they related to reproductive health and health care experiences. HyperRESEARCH 3.7.3 assisted in data organization and management. Limited bodily agency impacted women's ability to engage in family planning, particularly when partners utilized sexual coercion to maintain desired relationships and attain desired family size, regardless of women's preferences. In addition, limited sexual violence and abuse discussion in health care contexts impacted women's autonomy in reproductive health decision-making despite participants' desire to engage in these discussions with providers. Participants expressed a desire for communication about their sexual abuse experiences; however, results indicated women had to navigate stigma within families and communities, which deterred disclosure and open discussion. Negative health outcomes and desire to discuss these experiences within the health care context highlighted a need for patient–provider communication about sexual abuse history as one aspect of gynecologic care. Findings from this study offer practical recommendations to guide communication about sexual abuse within reproductive health care experiences to empower women in their reproductive health choices. As these experiences may impact overall health and reproductive choices, provider-initiated conversations with adolescents and women may improve care and assist in prevention efforts, including the prevention of negative health outcomes.